Effect of flash-calcined sediment substitution in sulfoaluminate cement mortar - Kleib, Joelle; Amar, Mouhamadou; Benzerzour, Mahfoud; Abriak, Nor-Edine (Frontiers in Materials, 2022)
Calcium sulfoaluminate cement is relatively a new type of cement with environmental advantages linked to its low carbon emission. However, there is a lack of knowledge on their use with supplementary cementitious materials (SCMs). This article aims to study the effect of utilizing activated flash calcined sediment from Noyelles-sous Lens (SC) as SCM in calcium sulfoaluminate mortar. Therefore, four mixes are prepared by replacing calcium sulfoaluminate cement 5, 10, and 20 % of flash-calcined sediment. The reactivity of the cement pastes with and without sediment was studied by isothermal calorimetry and by measuring the setting time. Then, the mechanical performances are tested at 1, 7, and 28 days. The results show that adding flash-calcined sediment has an accelerator effect on cement hydration and decreases the induction period. The cumulative heat release and the compressive strength at 28 days are almost the same, up to 10% of sediment substitution.